2022
DOI: 10.1098/rstb.2021.0433
|View full text |Cite
|
Sign up to set email alerts
|

Shodagor women cooperate across domains of work and childcare to solve an adaptive problem

Abstract: Across human societies, women's economic production and their contributions to childcare are critical in supporting reproductive fitness for themselves, their spouses and children. Yet, the necessity of performing both work and childcare tasks presents women with an adaptive problem in which they must determine how best to allocate their time and energy between these tasks. Women often use cooperative relationships with alloparents to solve this problem, but whether or not women cooperate across different doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Furthermore, women and girls are adept at exchanging cooperation across domains to balance multiple needs, such as childcare and productive labour. Starkweather and colleagues ([ 122 ], in this issue) showed that the cooperative childcare and work partner networks of Shodagor women in rural Bangladesh differed according to women's economic activities. Women who cooperated together as traders were also likely to provide childcare for each other.…”
Section: Key Themes and Findings From This Issuementioning
confidence: 99%
“…Furthermore, women and girls are adept at exchanging cooperation across domains to balance multiple needs, such as childcare and productive labour. Starkweather and colleagues ([ 122 ], in this issue) showed that the cooperative childcare and work partner networks of Shodagor women in rural Bangladesh differed according to women's economic activities. Women who cooperated together as traders were also likely to provide childcare for each other.…”
Section: Key Themes and Findings From This Issuementioning
confidence: 99%
“…Discussing null results is always challenging as there may be a number of ecological, theoretical and methodological reasons why our predictions were not supported. Ecologically, it may be that (fishing-focused) food production is not as incompatible with childcare in the Agta as we have assumed—as compatibility depends on the types of economic tasks (see [ 56 ] for discussion)—reducing the need to use childcare as a solution to food shortfalls. Certainly, in the coastal population, women often engaged in marine foraging in the inter-tidal zones, collecting shrimps, crabs, mollusc and octopus.…”
Section: Discussionmentioning
confidence: 99%
“…As we have not included in our analysis cooperation in food sharing, production and domestic labour we are ignoring the links between the layers in women's multiplex social networks. As argued by Atkisson and colleagues [ 63 ], this means we risk drawing the wrong conclusions because the cooperation that occurs in one domain can structure another [ 56 ]. Relatedly, a further issue is that the distinction between mobile and settled camps is not great enough in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations